looks like you got it.
dy/dx of :
y=cos(x) / (e^x) +1
__________________________________________
This is what I have got so far:
Use the quotient rule, so make u=cos(x) and make v=(e^x)+1
y=u/v
dy/dx = [(e^x)+1 * -sin(x) - cos(x) * e^x ] / ((e^x)+1)^2
What do I do next?
You did the quotient rule just fine, but I often avoid it if I'm not required to use it. Any quotient rule problem I've ever encountered can become a product rule + chain rule problem. Consider the following:
Then,
Much easier in my opinion, and you get the same answer.